Model' provedenija sorevnovanij ozdorovitel'noj napravlennosti (na primere bokserov-novikov) - Kim, V. V.; Kham, G. S.; Aminov, R. C.; Jusupov, R. R. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research was to show the efficiency of the organization and carrying out competitions of the improving orientation on the example of young male boxers-beginners.